Location! Location! Location! The Impact of Single-Room Design on Neurodevelopment of Preterm Infants. (1st June 2016) - Church, P; Ng, E; Weisz, D; Cavanagh, A; Dunn, M
Abstract: BACKGROUND: The impact of neonatal intensive care unit (NICU) design on neurodevelopmental outcomes of preterm infants is uncertain. Although single room design (SRD) reduces nosocomial infections and improves breastfeeding rates and parental satisfaction, recent data suggests that SRD may be associated with language delays and alterations in cortical development. OBJECTIVES: To compare neurodevelopmental outcomes of preterm infants who received care in a contemporary SRD environment compared with a similar cohort who received care during an earlier period with an open bay design (OBD). DESIGN/METHODS: Retrospective single-centre cohort study comparing the neurodevelopmental outcomes of all surviving extremely low birth weight (ELBW) i nfants admitted within 24 hours of birth in 2009 (OBD epoch) and 2011 (SRD epoch). The primary outcome was moderate or severe neurodevelopmental impairment using the Bayley Scales of Infant Development, third edition (BSID-III) at 18 months corrected age. Secondary outcomes included severe NDI and BSID-III scores. Multivariable logistic regression (MLR) analysis was used to evaluate the independent association between NICU design and outcomes. RESULTS: The study included 100 ELBW infants in 2009, and 98 in 2011. The 2 epochs were similar in follow-up rates (80% in 2009; 82% in 2011) and infant characteristics (including those lost to follow up). Mortality was 7.9% in 2009 and 6.1% in 2011. BSID-III language scores (median [interquartile range]) were similar for infants in the OBD and SRD epochs (86 [71, 100] vs. 81 [71, 94], p=NS). On MLR analysis, NICU design was not associated with significant differences in NDI or BSID-III language score less than 80 after adjustment for antenatal and perinatal confounders. (Table1) CONCLUSION: There was no significant difference in NDI between cohorts of ELBW infants cared for in an SRD compared with an OBD NICU design environment. The contrast in findings from earlier studies may be attributable to the local context of government-supported parental leave and strong promotion of parental presence in the NICU.